As Áreas de Preservação Permanente (APPs) ao longo dos cursos d'água em área urbana: uma análise sob a ótica do Novo Código Florestal (Lei nº 12.651/2012) e da Lei de Uso e Parcelamento do Solo Urbano (Lei nº 6.766/1979) - Hobold, Caroline (2018)
The concept and delimitation of Permanent Preservation Areas through the courses of water can be found at the new forestall code (Law n. 12.651/12). However, despite the existence of this delimitation, the Law For Use and Installment of the Urban Soil (Lei nº 6.766/1979), predicts a protection distance for the APPs (Permanent Preservation Areas) diverse of those presented by the federal environmental law, and that, generated an antinomy between these norms. Therefore, this work had the objective of identify what is the applicable delimitation to the permanent preservation areas through the courses of water, at urban areas, analyzing what is disposed at the the Law For Use and Installment of the Urban Soil and at the New Forrestal Code, in order to overcome the existing conflict. The present research was made from the legal, doctrinaire and jurisprudential analysis about the approached theme, utilizing the inductive examination method and the comparative method, making a qualitative analysis of the results gotten. After a deep study about the theme, the conclusion is that the disposal of general environmental parameters, like the Forrestal Code presents, it’s not the most correct and effective way for the preservation of the environment. The characterization of The APPs (Permanent Preservation Areas) is based on the environmental function. And for this analysis, it must be observed if the APP is really accomplishing the function determined to itself. Consequentially, in relation to the consolidated urban areas, it became reasonableness to impose the protection margin predicted on the ambiental legislation, leading to the application of the specific disposal settled at the Municipal Management Plan.